Co-Composted Fecal Sludge Based Integrated Nutrient Management for Sustainable Aman Rice Production - Mahmud, Nayma Binta; Anwar, Md Parvez; Yeasmin, Sabina; Sultana, Nasrin; Ghosh, Susmita; Islam, A K M Mominul; Jaman, Md Sunain Bin (Journal of Science and Technology Research, 2024)
This study was undertaken to judge the efficacy and economic feasibility of cocomposted fecal sludge (CCFS) in increasing growth and productivity of transplant Aman (T. Aman) rice and to optimize CCFS dose for integration with chemical fertilizers to maximize T. Aman rice yield and economic return. This study was consisted of two factors included two T. Aman rice varieties namely, BRRI dhan 49 and Dhanigold; and 10 chemical fertilizer+CCFS combinations such as, recommended dose of synthetic fertilizer (RDF), CCFS @ 5 t ha-1, RDF+CCFS @ 2 t ha-1, RDF+CCFS @ 1.5 t ha-1, RDF+CCFS @ 1 t ha-1, RDF+CCFS @ 0.5 t ha-1, 75% RDF+CCFS @ 2 t ha-1, 75% RDF+CCFS @ 1.5 t ha-1, 75% RDF+CCFS @ 1 t ha-1 and 75% RDF+CCFS @ 0.5 t ha-1. A clear advantage of integrating CCFS with chemical fertilizers to increase rice growth and yield was evident in this study. The highest grain yield was recorded when CCFS @ 2 t ha-1 was integrated with recommended chemical fertilizers, and that was >7% higher than that obtained from the application of only recommended chemical fertilizers. But application of only CCFS @ 5 t ha-1 reduced grain yield by as much as 47%. The highest benefit:cost ratio for BRRI dhan49 and Dhanigold (1.66 and 1.61, respectively) were calculated from recommended chemical fertilizers application closely followed by application of recommended chemical fertilizers+CCFS @ 2 t ha-1 (1.55 and 1.49, respectively). In case of both the varieties, application of only CCFS @ 5 t ha-1 resulted in negative net return and <1 benefit:cost ratio (0.75 and 0.73, respectively for BRRI dhan 49 and Dhanigold) due to poorer yield and higher cost for CCFS. Encouraging findings of this study confirm that CCFS obtained from faecal sludge can be integrated with chemical fertilizers to increase the productivity of T. Aman rice. In terms of grain yield, recommended chemical fertilizers+CCFS @ 2 t ha-1 appeared as the best option, but application of only recommended chemical fertilizers was found a bit more economic than integration. Application of only CCFS without chemical fertilizers was found neither productive nor economic. To conclude, co-compost can be used to supplement chemical fertilizers for in rice cultivation, and thus will contribute to green agriculture by improving soil health and minimizing environmental pollution. It is therefore necessary to conduct multi-location trials for consecutive years on other crops as well to confirm the potentiality of co-compost as a manure to increase crop productivity, and as a soil conditioner for soil health improvement. J. of Sci. and Tech. Res. 6(1): 149-159, 2024